Razmyšleniâ nad voprosom o sootnošenii funkcionalʹnoj stilistiki i diskursnyh issledovanij (s rečevedčeskih pozicij) - Kožina, Margarita N. (Stylistyka, 2021)
The article considers the question of the correlation of the subject and research methodology of functional stylistics and discourse analysis (primarily French tradition of discourse analysis - DA). It takes into account the change of modem linguistics from a structural paradigm to a functional one. It states the compared subjects refer to speech studies (speech linguistics) and account for the process of speech activity and its extralinguistic factors. It also proposes the definition of «discourse» . The emphasis is that unlike traditional stylistics which P. Serio distanced away from, modem works on functional stylistics are close to discourse analysis (DA).